Comparison of anatomical locations of cutaneous melanoma in men and women: a population‐based study in France. (16th August 2014) - Chevalier, V.; Barbe, C.; Le Clainche, A.; Arnoult, G.; Bernard, P.; Hibon, E.; Grange, F.
Abstract : What's already known about this topic? The predominance of melanomas on the trunk in men and on the lower limbs in women has been reported for a long time, and was recently found to decrease in some developed countries. Few population‐based studies have compared the precise location and side between the sexes. What does this study add? Women had more frequent melanomas on the lower limb, the hand and foot, and the central area and right side of the head and neck. Melanomas of the trunk, the peripheral area, and left side of the head and neck were more frequent in men. The distribution of foot melanoma differed between the sexes. Different patterns of ultraviolet and sun exposure suggest the usefulness of sex‐specific advice for melanoma prevention. Summary: Background: Identification of differences in melanoma location between the sexes could lead to sex‐specific preventive measures. Objectives: To compare precise melanoma location and side in men and women. Methods: The location of 1542 incident melanomas diagnosed during the period 2004–2011 in the French Champagne‐Ardenne region (1·3 million inhabitants) was recorded using a regional registry and questionnaires sent to physicians. Men and women were compared for frequency of tumours on the head and neck; trunk; upper limb; lower limb; hand and foot. For each location, more precise sublocations were recorded. The laterality (right vs. left) was studied for head/neck and limb tumours. Results: Melanomas predominated on the lower limb in women (32·2% vs. 9·3% in men; P  <   0·01) and on the trunk in men (41·8% vs. 14·9%; P  <   0·01), while the proportion of upper limb and head/neck tumours was similar in both sexes. Hand and foot melanomas predominated in women (10·3% vs. 6·3%; P  <   0·01), with a sex‐related distribution between sublocations. Within the head and neck location, 75·1% of tumours in women were located in the central area vs. 53·7% in the peripheral area in men ( P  <   0·01). Head and neck melanomas were more frequently right‐sided in women and left‐sided in men ( P  =   0·04), with the left/right ratio reaching 1·58 in men vs. 0·61 in women for peripheral tumours ( P  <   0·01). No difference in laterality was observed for other locations. Conclusions: Sex differences in occupational and leisure time ultraviolet exposure, clothing (including shoes), hairstyle, and side and photo exposure in cars could explain these results. General preventive messages could be completed by sex‐specific advice for melanoma prevention.